2005
DOI: 10.1183/09031936.05.00127704
|View full text |Cite
|
Sign up to set email alerts
|

Non-CF bronchiectasis: does knowing the aetiology lead to changes in management?

Abstract: The aim of the current study was to review the aetiology of non-cystic fibrosis (CF) bronchiectasis from two tertiary paediatric respiratory units in order to determine how often making a specific aetiological diagnosis leads to a change in management, and to assess the contribution of computed tomography (CT) in determining the underlying diagnosis.The case records of all patients who were diagnosed as having bronchiectasis by CT, currently being seen at the Royal Brompton Hospital and Great Ormond Street Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
168
6
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(199 citation statements)
references
References 37 publications
(37 reference statements)
14
168
6
11
Order By: Relevance
“…There was no aspiration case due to neurologic reasons. Zaid et al 19 reported rate of BE secondary to aspiration as 22% and Li et al 20 as 18%. In the studies from our country, Karadağ et al 16 reported the rate as 3.6% and Doğru et al 18 as 3.4% but Karakoç et al 17 reported no case of BE secondary to aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…There was no aspiration case due to neurologic reasons. Zaid et al 19 reported rate of BE secondary to aspiration as 22% and Li et al 20 as 18%. In the studies from our country, Karadağ et al 16 reported the rate as 3.6% and Doğru et al 18 as 3.4% but Karakoç et al 17 reported no case of BE secondary to aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of bronchiectasis in other rare PIDs such as hyper-IgE syndrome (<2.5% in children and very rare in adults) [74,84,85], phagocyte defects (<1%-10% in children and <1% in adults) [86,87], and transporter antigen peptide deficiency (rare in children and very rare in adults) [87,88] is low. The microorganisms associated with bronchiectasis in patients with PID are shown in the Table. High-resolution computed tomography (HRCT) is considered a reliable test for assessing bronchiectasis in patients with PID [89][90][91].…”
Section: Bronchiectasismentioning
confidence: 99%
“…More than 70% of CVID patients develop bronchiectasis and bronchial wall thickening [47,72], indicating that bronchiectasis is a well-recognized complication of CVID. The incidence of bronchiectasis in patients with XLA is almost 32%, although XLA has been associated with up to 3% of cases of childhood bronchiectasis [73][74][75] and is rare in adults. We indicated that the rate and severity of bronchiectasis were greater in CVID patients than in those with XLA, probably because of the earlier diagnosis and treatment of XLA patients [76].…”
Section: Bronchiectasismentioning
confidence: 99%
“…Su frecuencia oscila, en adultos y niños, en 0-17%. 18,[40][41][42] Dentro de las adquiridas, además de la inmunodepresión farmacológica, destaca la infección VIH (sida). Las bronquiectasias son más frecuentes en pacientes con neumonía intersticial linfoide, neumonías bacterianas o protozoarias recurrentes, o mayor grado de inmunodepresión, especialmente si los linfocitos CD 4+ son menores de 100/mcL.…”
Section: Inmunodeficienciasunclassified
“…43,44 De las congénitas, las humorales son las que más se asocian a bronquiectasias, destacando la agammaglobulinemia ligada al cromosoma X, la inmunodeficiencia común variable, y déficit de subclases de inmunoglobulinas. 18,[40][41][42] El déficit de IgA, déficit inmunológico más frecuente, se ha asociado a bronquiectasias, pero existe discrepancia al respecto. 45,46 Los gérmenes son clásicamente encapsulados (S. pneumoniae, H. influenzae).…”
Section: Inmunodeficienciasunclassified